ANALISIS KESULITAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI OPERASI BILANGAN BULAT - Malichatuz Zahro Assaidah, Syarifah Nur Aulia, Erika Diah Pangestuti, Diana Ermawati (CV. ADIBA AISHA AMIRA, 2024)
This research is motivated by the low problem-solving ability of students. The purpose of this study is to obtain an overview of students' difficulties in solving mathematical problems related to integer operations in the fourth-grade class at SDN 2 Klaling. The method used in this research is a descriptive qualitative method. Data were obtained using interview, observation, and documentation techniques. fourth-grade teachers at SDN 2 Klaling, and secondary data in the form of books, journals, documentation, and references about students' problems in the integer operations material. Meanwhile, the data analysis technique in this study uses the interactive data analysis model of Miles & Huberman, which explains that interactive data analysis techniques consist of three components: data reduction, data presentation, and conclusion drawing. The results of this study show that students still have difficulty understanding the meaning of symbols and parentheses when working on integer division problems. Students also experience difficulties in operating numbers with negative signs in the material on subtraction and addition of integers. The difficulties in understanding mathematical concepts are due to both internal and external factors.